Antimicrobial Activity of Hydroxymatairesinol (HMR) Lignan# - Widad M.K. Al-Ani; Fitua M. Aziz (College of Pharmacy University of Baghdad, 2017)
Lignans are natural products widely distributed in the plant kingdom. They are composed of two Î²-Î²-linked phenylpropane (shikimate-derived biogenetic subunits). Although the backbone of lignans is composed of phenylpropane units, there is enormous diversity in the structure of lignans leading to different classes of lignans, such as Î³-butyrolactone derivatives, eg. Hymatairesinol, bicyclooctadiene derivatives, e.g. pinoresinol, tetrahydrofuran derivatives e.g.lariciresinol, di-arylbutandiol derivatives, e.g. secoisolariciresinol. Introduction of a further carbon â€"carbon linkage leads to a class of lignans collectively known as cyclolignans such as tetrahydro-naphthalene derivatives, for example podophyllotoxin. Lignans have a broad range of biological activities; many of them show significant antitumour, antimitotic, and antiviral effects. They also have cardiovascular effects, antimicrobial and insecticidal activities. The efflux mechanisms of bacteria to some antibiotics and resistance of bacteria to many antibiotics led to search for antibacterial compound of plant origin to overcome these problems. The antibacterial activity of HMR lignan was determined using the disc diffusion method and the MIC of the isolated compound was tested by the broth micro-dilution method. HMR lignan showed activity against Staphylococcus epidermidis(17 mm), Candida albicans (13mm), Proteussp(12mm) and Klebsiella sp (12mm). Key words: Lignans, Hydroxymatiaresinol, Antimicrobial activity